2011
DOI: 10.1590/s0103-64402011000600008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermocycling and light source on the bond strength of metallic brackets to bovine teeth

Abstract: This study evaluated the effects of thermocycling and different light sources on the bond strength of metallic brackets to bovine tooth enamel using an adhesive resin. Bovine teeth were etched with 35% phosphoric acid gel for 20 s. After application of primer, metallic brackets were bonded to the buccal surface using Transbond XT, forming 8 groups (n=20), depending on the light source used for photoactivation (AccuCure 3000 argon laser - 20 s, Apollo 95E plasma arc - 12 s, UltraLume 5 LED - 40 s and XL2500 hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…However, several studies showed no significant differences among different light sources (6,7,17,18). Other studies showed that the absence of differences probably might be explained by the fact that a very thin resin layer is necessary for bracket bonding and, thus, the differences in energy dose were probably not enough to influence the bond strengths (7,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies showed no significant differences among different light sources (6,7,17,18). Other studies showed that the absence of differences probably might be explained by the fact that a very thin resin layer is necessary for bracket bonding and, thus, the differences in energy dose were probably not enough to influence the bond strengths (7,19).…”
Section: Discussionmentioning
confidence: 99%
“…The composite resins are densely loaded with reinforcing filler particles for strength and wear resistance 7 . The advantage of light-activated composite resins is that the clinician has time to place the brackets in the position, may remove excess material before the light activation 8 , and support adequately the loads applied during orthodontic treatment resulting from chewing 9 . However, failures with composite resins can occur and has been attribute to humidity contamination 10 or incomplete polymerization when considering the light exposure time or limited depth polymerization 11 , which changes with the light penetration into the material 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The light-cured composite resins are routinely used for bonding orthodontic brackets to the teeth (1,2). The advantage of light-cured composite is that the clinician has enough time to place the brackets in the correct position and easily remove any excess material before the lightactivation and insertion of the orthodontic archwire (3).…”
Section: Introductionmentioning
confidence: 99%